STUDI EKOHIDROLOGI ’EMBUNG’ SIRANI HALIWEN BAGI PENGEMBANGAN EKOWISATA DI KABUPATEN BELU - NTT - Widiyono, Wahyu (Jurnal Hidrosfir Indonesia, 2009)
‘Embung’ Sirani, located 10 km from the capital city of Belu District, East Nusa Tenggara Province, is the biggest of the 27 ‘embungs’ in this area. The ‘embung’ has 211.2 of watershed area, 20 m of water depth and 1.860.000 m3 of water storage capacity to irigate rice field. To promote the unic and strategic ‘embung’ as an ecotorism object, an ecohydrologic study was conducted in 2008. Ecotourism objects which can be developed around the Sirani ‘embung’ in Belu Districts are the lake tourism, canoe ride around the ‘embung’; agro-tourism of horticulture plant and fishing pond at the ‘embung’ downstream; and agroforestry-tourism at the watershed area. ‘Embung’ ecotourism as an integrated conservation by participation of the local people is needed to develop.